Synthesis of Extra-large Pore of Zeolite Mineral - 张铨昌 刘蔚玲 韩成 张振禹 徐晓岚 (中国科学通报：英文版, 1994)
In the late 1970s, the discovery of the alumindnophosphate molecular sieveminerals which have been called a new generation led to framework composition oxideoutside of the aluminium-silicon system. The largest secondary building unit (SBU)of 18 T-atom rings has been maintained more than 180 years[2]. Only just in 1988,the molecular sieve with eighteen membered-ringr was reported by Davis and calledVIP-5 after the Virginia Polytechnic Institute. But a dissent has been expressed byDuncan for this. It was considered that VPI-5 does not represent a new